Determinação de As, Sb e Se em material agronômico por espectrometria de emissão óptica acoplada a plasma induzido com geração de hidretos (HG-ICP-OES) - Crispino, Carla Cripa (Universidade Federal de São Carlos, 2005)
With the objective to attain maximum productivity with small costs, organic and inorganic chemical parameters are used to evaluate and monitoring crops and animals development. Inorganic amounts in agronomic samples have great importance in the production evaluation. Some of elements in those samples could be an indicative of quality, owing to their requirement (Se) or toxicity (As, Sb), even when they are present in µg kg-1 levels, needing a technique with high sensibility for quantification. The aim of this work was the development of a simple system of hydride generation by continuous flow combined with an inductively coupled plasma optical emission spectrometry for simultaneous determination of As, Sb and Se in agronomic samples. The work attained to a gas-liquid separator development, and an experimental planning to established the chemical and instrumental conditions of hydride generation. The HCl, NaBH4 and KI concentrations, such as the R.F. power, carrier gas flow and the viewing height, were evaluated besides the study of a more appropriate sample preparation. Limits of detection of the proposed system were 0.1 µg L-1 for As, Sb and Se and the limits of quantification were 0.3, 0.2 and 0.2 µg L-1 for As, Sb and Se respectively with RSD smaller than 10% and 30 samples per hour of reading speed. In view to observe the accuracy, four different kinds of samples forage and bovine-derived samples (blood, viscera and semen) were spiking with analytes concentration in the µg L-1 level. Recoveries around 77 to 112% were found. The results present the possibility to use the proposed system in agronomic projects developed with the objective to determine essential and toxic analytes in different kinds of feed and animal samples, contributing to evaluation of nutritional demands and the increase of efficiency in the bovine production systems.
Determination of As, Sb and Se in agronomic samples by hydride generation inductively coupled plasma optical emission spectrometry
Keywords: Química analítica; Geração de hidretos; Arsênio; Selênio; ICP-OES; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA